KEPENTINGAN THAILAND DALAM PENERAPAN KEBIJAKAN LEGALISASI GANJA - Kama, I Putu Satya; Intan Prameswari, Anak Agung Ayu; Sushanti, Sukma (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2021)
Thailand was one of the biggest cannabis producing countries in the world in the 80s. After signing the UN regulations on drugs (Narcotics, Psychotropics and Addictive Substances), Thailand made new regulations and strongly opposed the distribution of cannabis in the country. By implementing a